2021
DOI: 10.47869/tcsj.72.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to mask wearing on public transport during the COVID-19 pandemic and influential factors: the case of Hanoi

Abstract: In response to little known about the use of face masks for public transport passengers in developing countries, this study investigates the prevalence of using masks and using masks correctly together with influential factors. Using 570-passenger data collected on the whole bus network from 7 September to 3 October 2020 in Hanoi, the authors found that 100% of users wore masks; however, about 11% failed to wear masks correctly. As regards factors, passengers who are old, rarely ride by bus, take heavy luggage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…On public transport, face masks have been mandatory and this rule has been strictly enforced. One study (Manh et al 2021 ) reported that the rate of mask wearing is 100% on-board with nearly 90% of passengers using masks correctly. As a consequence, no cases of infection have been detected on public transport and the perception of risk has been minimized.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…On public transport, face masks have been mandatory and this rule has been strictly enforced. One study (Manh et al 2021 ) reported that the rate of mask wearing is 100% on-board with nearly 90% of passengers using masks correctly. As a consequence, no cases of infection have been detected on public transport and the perception of risk has been minimized.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…To prevent the transmission of the coronavirus, the government of Vietnam decided to apply social distancing from 31 March to 30 April 2020 [26]. To investigate the impacts of COVID-19 on inhabitants' daily lives in Hanoi, we carried out a four-week survey between 6 and 30 April 2020 to collect data on the realities of e-activities.…”
Section: Datamentioning
confidence: 99%
“…First detected in Wuhan in December 2019, a highly infectious disease caused by a new coronavirus (SARS-CoV-2) rapidly escalated into a pandemic, officially named COVID-19 [23]. To combat the "public health emergency of international concern" declared by the World Health Organization, a series of interventions and recommendations at different degrees (e.g., wearing masks, working from home, social distancing, and lockdown) to limit physical interactions between citizens have been issued [24][25][26]. In adapting to the context of mobility restrictions, people have been accelerating the use of ICT to perform daily activities, such as shopping [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Offering masks at the stations might be especially valuable for these groups. Furthermore, the study of Huu Manh et al (2021) suggests that communication does not end with only wearing the mask, but also prompting to wear masks correctly could contribute to decreasing the objective risk in public transport. In their study, 11% of passengers failed to wear the mask correctly, especially passengers who were older, rarely used public transport, transported heavy luggage, or traveled with others.…”
Section: Using Communication To Decrease the Objective Risk In Public...mentioning
confidence: 99%